ASSOCIATION BETWEEN ALPHA-FETOPROTEIN AND OTHER SEROLOGICAL MARKERS IN PATIENTS WITH HEPATOCELLULAR CARCINOMA: ONE CENTER'S EXPERIENCE - Lejla Mehinović; Zora Vukobrat-Bijedić; Azra Husić-Selimović; Amina Kurtović-Kozarić; Erna Islamagić; Damir Suljević (Peytchinski Publishing, 2018)
Purpose: In this study, we analyzed biochemical parameters in the serum of patients with a diagnosis of hepatocellular carcinoma (HCC) C and B viral aetiology. Material/Methods: All patients (31 males and 20 females) with a diagnosis of HCC that were treated at the Clinical Centre of the University of Sarajevo were included in this retrospective-prospective study. Serum alpha-fetoprotein was analyzed as a tumour marker, and hepatitis markers included HBs Ag, anti-HBs, anti-HBc, anti-HCV and anti-HB. Spearman test and Kolmogorov-Smirnov test were used for correlation and normality analysis, respectively. Results: The largest number of patients (68.62%) had cirrhosis of C viral aetiology that developed in cancer. Hepatocellular carcinoma was diagnosed more in men than in women (60.78%). The most patients were middle-aged (41-64 years). HCC was present in the right liver lobe at 82.85% HCV and 87.5% HBV patients. Only 6.25% of HBV patients were both liver lobes affected. All biochemical parameters had very high values, especially AFP and γGT. Significant differences for AST and ALT were found between men and women. Serum bilirubin levels (total, direct and indirect) and AP are higher in men than in women. Hepatitis markers had high values, and the incidence of HBs Ag (78%) and anti-HBc (78.72%) was established. Conclusions: A positive correlation was established between AFP and other parameters, while a significant difference between AFP and γGT (r = 0.372, p = 0.008) was confirmed. In addition to imaging methods for determining liver cirrhosis and hepatocellular carcinoma, high values of AFP and γGT, are a powerful diagnostic marker for these diseases.